Penerapan Model Problem Based Learning Berbantuan Geogebra Untuk Meningkatkan Hasil Belajar Peserta Didik - Hardianti, Anggi; Fatqurhohman, Fatqurhohman; Juliastuti, Ika Aldrina (Media Pendidikan Matematika, 2025)
This study aims to describe the application of the Geogebra-assisted Problem Based Learning model to improve student learning outcomes in the exponential function graph material of class XI-6 SMAN Pakusari, Jember Regency. This study was conducted in two cycles using a collaborative classroom action research methodology. The data analysis techniques used were qualitative and quantitative data analysis. Data were collected through observation sheets of 36 students, consisting of 9 males and 27 females. The results of the study showed an increase in student learning outcomes, with an average student learning outcome in the pre-cycle stage of 61.34, increasing to 68.92 in cycle I, then increasing to 86.77 in cycle II. Based on the results of the study, it can be concluded that the application of the Geogebra-assisted Problem Based Learning model can improve student learning outcomes in the exponential function graph material